In-situ test method for researching electron transport mechanism of SrTiO3atAg nanotube photocatalyst with oxygen vacancy modification
Through the synergistic strategy of oxygen vacancies and Schottky junction, SrTiO3@Ag nanotubes were prepared, which solved the problems of narrow light absorption range, low carrier concentration and serious photogenerated electron-hole recombination of the existing SrTiO3 photocatalysts, achieving efficient photocatalytic activity improvement.
Patent Information
- Application Number
- CN202510124806.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-26
AI Technical Summary
The existing SrTiO3 photocatalysts have problems such as narrow light absorption range, low carrier concentration and serious photogenerated electron-hole recombination, resulting in low photocatalytic activity.
Through the synergistic strategy of oxygen vacancy modification and Schottky junction, SrTiO3@Ag nanotubes were prepared, and photogenerated electrons were captured using oxygen vacancy and transferred to Ag nanoparticles, achieving spatial separation of photogenerated charges, and studying the migration direction of photogenerated electrons by in-situ irradiation XPS.
The photoabsorption capacity and carrier concentration of the photocatalyst are significantly improved, the recombination of photogenerated electrons and holes is inhibited, and the photocatalytic activity is improved, especially the performance under ultraviolet light irradiation is significantly improved.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
[0001] The invention relates to the technical field of energy materials, and in particular to a method for preparing SrTiO3@Ag nanotubes modified with oxygen vacancies and the application of in-situ irradiation XPS in mechanism research. Background Art
[0002] Energy is one of the important factors that promote the progress and development of human civilization. It has always been accompanied by the utilization, processing, conversion and innovative development of energy. However, with the growth of the global population and the acceleration of industrialization, energy shortage and environmental pollution are two key issues that need to be solved urgently. In order to achieve green and low-carbon sustainable development, it is a promising new technology to convert solar energy into chemical energy with stable storage, convenient access and high energy density by simulating photosynthesis in nature. The development of low-cost, stable and efficient photocatalysts to meet the needs of further applications is the research focus of photocatalysis.
[0003] Among many photocatalysts, strontium titanate (SrTiO3) is a transition metal oxide with a perovskite structure. It stands out for its excellent photocorrosion resistance and high thermal stability. However, due to its wide band gap, it only responds to ultraviolet light with higher energy, so the light absorption range is narrow; the recombination of photogenerated electrons and holes in the body is serious, and the ability to promote charge separation is weak; the number of photocatalytic active sites of traditional SrTiO3 powder materials is insufficient and easy to agglomerate, resulting in many limitations when SrTiO3 is used alone as a photocatalyst, resulting in low photocatalytic activity. Therefore, based on the principle of photocatalysis and the current research status, constructing heterojunctions and defect engineering are effective strategies to improve photocatalytic activity. One-dimensional semiconductor nanotubes have excellent morphological and structural characteristics such as high aspect ratio, large specific surface area and short electron migration distance, which can be used to upgrade SrTiO3 powder materials. In order to inhibit the recombination of photogenerated electron-hole pairs and to effectively adjust the electronic structure of SrTiO3 semiconductors to increase the carrier concentration, it is very necessary to directly apply defect engineering strategies to the modification of SrTiO3 nanotubes. Through oxygen vacancy defect engineering, it is expected that the photocatalytic activity of wide bandgap semiconductor SrTiO3 can be effectively improved, which is limited by narrow light absorption range, low carrier concentration, and rapid photogenerated carrier recombination. At the same time, it can also greatly affect the physicochemical properties of SrTiO3, including intrinsic electronic structure, charge migration and surface state.
[0004] In addition, modifying SrTiO3 by loading highly conductive materials on its surface is a method to improve its photocatalytic performance. An attractive strategy is to transfer photogenerated electrons in the conduction band of SrTiO3 to the conductor loaded on its surface. Inhibits the recombination of photogenerated electrons and holes. Among highly conductive materials, Ag has excellent conductivity and stable It has chemical properties and is a suitable co-catalyst material. It has been widely used to enhance the photocatalytic activity of semiconductors. Moreover, the combination of Ag nanoparticles and SrTiO3 semiconductors can form a Schottky junction at the heterojunction interface, thereby effectively enhancing the separation of photogenerated electrons and holes.
[0005] The purpose of the present invention is to provide an in-situ test method for studying a reliable and convenient electron transport path, which is used to study the electron transport mechanism of oxygen vacancy modified SrTiO3@Ag nanotube photocatalyst. Therefore, this paper adopts an electrospinning process to prepare SrTiO3 hollow nanotubes using a sacrificial template method. On this basis, oxygen vacancies are introduced by heat treatment in an argon-hydrogen mixed atmosphere, and the oxygen vacancy concentration is controlled by the heat treatment temperature. After oxygen vacancy modification, the oxygen vacancies can capture the activated photogenerated electrons in the SrTiO3 nanotubes and transfer them to the Ag nanoparticles anchored near them for photocatalytic reduction reaction, effectively realizing the spatial separation of photogenerated charges. At the same time, the presence of Schottky barriers at the heterojunction interface also inhibits the photogenerated electrons from flowing back to the SrTiO3 nanotubes, thereby preventing the recombination of photogenerated electrons and holes. This invention uses defect engineering and Schottky junctions to synergistically improve the photocatalytic performance, and studies the migration direction of photogenerated electrons under 350 nm ultraviolet light irradiation by in-situ irradiation XPS, which provides a solution for the rational design of photocatalysts with efficient charge carrier dynamics for solar energy conversion. Summary of the invention
[0006] In order to achieve the above object, the present invention provides the following scheme: An in-situ test method for studying the electron transport mechanism of SrTiO3@Ag nanotube photocatalysts with oxygen vacancies. The steps are as follows: (1) Synthesis of oxygen vacancy modified SrTiO3@Ag nanotubes: Strontium acetate was dissolved in a mixed solution of deionized water, anhydrous ethanol, N,N-dimethylformamide and glacial acetic acid, and polyvinyl pyrrolidone was slowly added. After stirring, butyl titanate was added and continued to stir until a uniform translucent solution was formed. The solution was electrospun to form a pure white polymer film, which was then dried and collected in a crucible for calcination to remove the PVP template to obtain SrTiO3 nanotubes. The solution was then reduced with high-temperature H2 and dispersed in a AgNO3 solution with continuous stirring. The suspension was then irradiated with ultraviolet light and continuously magnetically stirred. Finally, the product was separated from the liquid and washed with water several times before drying to obtain oxygen vacancy modified SrTiO3@Ag nanotubes. (2) Study on the mechanism of oxygen vacancy modification of SrTiO3@Ag nanotubes: UV irradiation was introduced, and the photogenerated electron transfer behavior was studied through in-situ XPS testing. The changes in the binding energy of the components before and after irradiation were observed to determine the electron gain and loss situation. The research equipment used was an original light source with a light-guiding optical fiber installed in the equipment, and the light was irradiated onto the sample in the test chamber through the equipment observation window.
[0007] In step (1), the stirring time is 8 to 12 h, the drying temperature is 50 to 60 ° C, the drying time is 10 to 15 h, the calcination time is 2 to 5 h, and the calcination temperature is 500 to 700 ° C.
[0008] Furthermore, the calcination process in step (1) is to heat the mixture in a muffle furnace at a heating rate of 1 to 3 °C / min to 500 to 700 °C and keep the temperature for 2 to 5 hours. Each gram of strontium acetate is dissolved in 5 to 6 mL of deionized water, and then anhydrous ethanol, dimethylformamide and glacial acetic acid are added in sequence and stirred and mixed. Polyvinyl pyrrolidone is slowly added to the mixed solution, and then magnetic stirring is performed for a long time, the stirring time is 8 to 12 hours, and finally butyl titanate is added and stirring is continued until a uniform light yellow translucent solution is formed.
[0009] Furthermore, in step (1), the SrTiO3 nanotubes are evenly spread in a porcelain boat and placed in a tube furnace, and the air in the tube furnace is exhausted by a vacuum pump, and then an argon-hydrogen mixture (H25%, Ar 95%) is continuously supplied at a certain rate. The temperature is raised to 400-800 °C at a rate of 5-10 °C / min and kept warm for 1-3 h. The sample is prepared by a photoreduction method based on oxygen vacancy modified SrTiO3 nanotubes. Specifically, the sample is dispersed in an AgNO3 solution and stirred continuously to fully adsorb Ag+, and then the suspension is irradiated with 365 nm ultraviolet light, and magnetic stirring is continuously performed during the irradiation process. Finally, the sample is separated from the liquid and washed with deionized water for multiple times and then dried.
[0010] Furthermore, in step (2), 350 nm ultraviolet light irradiation is introduced during the test process, and the electron gain and loss situation is determined by observing the change in the binding energy of the components before and after irradiation.
[0011] The beneficial effects of the present invention are: The present invention studies the migration direction of photogenerated electrons under ultraviolet irradiation by in-situ irradiation XPS, confirms the electron flow direction from semiconductor SrTiO3 nanotubes to metal Ag single substance, and reveals the reason for the improvement of composite photocatalyst activity. The present invention judges the electron gain and loss by observing the change of component binding energy before and after in-situ irradiation test. The oxygen vacancies in the material system can capture the photogenerated electrons activated in the SrTiO3 nanotubes and transfer them to the Ag nanoparticles anchored near them for photocatalytic reduction reaction, effectively realizing the spatial separation of photogenerated charges. According to the electron shielding effect, the change of outer electron density caused by the transmission of electrons between components is finally reflected in the binding energy of the test element. The increase of binding energy indicates the outflow of electrons, and vice versa.
[0012] The present invention provides an in-situ testing method for studying the electron transport mechanism of SrTiO3@Ag nanotube photocatalyst modified with oxygen vacancies. The research method adopts in-situ irradiation XPS technology, and studies the migration direction of photogenerated electrons under 350 nm ultraviolet light according to the characteristics of the material. Therefore, the present invention adopts in-situ electrostatic spinning technology to prepare SrTiO3 nanotubes of white matter. The PVP micelle template is removed by calcination; oxygen vacancies are introduced by heat treatment under an argon-hydrogen mixed atmosphere, and after the oxygen vacancies are modified, Ag nanoparticles are deposited on the surface of the SrTiO3 nanotubes by a photoreduction method. In the material system, oxygen vacancies can capture photogenerated electrons activated in the SrTiO3 nanotubes and transfer them to Ag nanoparticles anchored near them for photocatalytic reduction reaction, effectively realizing the spatial separation of photogenerated charges. Light absorption is significantly improved, and the utilization rate of visible light is improved, which is conducive to the activation of more photogenerated electrons and holes. At the same time, the presence of the Schottky barrier at the heterojunction interface also inhibits the photogenerated electrons from flowing back to the SrTiO3 nanotubes, thereby preventing the recombination of photogenerated electrons and holes, thereby promoting the photocatalytic reaction. The in-situ irradiation XPS method was used to reveal the reason for the improvement of the activity of the composite photocatalyst.
[0013] The in-situ mechanism research method provided by the present invention has the following characteristics: (1) Compared with the ordinary XPS test method, the light-adding experimental method can better simulate the scene of the actual use of the photocatalyst. (2) The traditional mechanism research method cannot accurately describe the transmission path of electrons under the dual effects of oxygen vacancy modification and Schottky binding, which brings great difficulties to the mechanism research, while the XPS test method can reflect the electron transmission direction according to the change of binding energy.
[0014] The photocatalytic performance of the oxygen vacancy modified SrTiO3@Ag nanotubes prepared by the present invention and the SrTiO3 catalyst were compared under the same conditions. The modified sample with the best performance had a hydrogen evolution rate of 55.92 µmol / g / h, which was 6.28 times that of the original SrTiO3 nanotubes, and showed good cycle stability, which is beneficial to the practical application of photocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 (a) XRD patterns of prepared SrTiO3@Ag nanotubes modified with oxygen vacancies and different samples; (b) shows that the interplanar spacing of the hydrogenated samples is reduced and contains abundant oxygen vacancies. (c) PL spectra of photocatalysts of different samples; (d) transient photocurrent response; Figure 2 (a, b) TEM images of SrTiO3@Ag nanotubes modified with oxygen vacancies prepared in Example 2; Figure 3 Photocatalytic hydrogen evolution performance test of different samples (a) Time course curve of photocatalytic hydrogen evolution; (b) Corresponding average rate of photocatalytic hydrogen evolution; Figure 4 Schematic diagram of the in-situ irradiation XPS device; Figure 5 The figure shows the in-situ irradiation XPS spectrum of the SrTiO3@Ag nanotubes modified with oxygen vacancies prepared in Example 2: (a) Sr 3d; (b) Ti 2p; (c) O 1s. DETAILED DESCRIPTION
[0016] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] The invention discloses an in-situ test method for studying the electron transport mechanism of SrTiO3@Ag nanotube photocatalyst modified with oxygen vacancies. SrTiO3@Ag nanotubes modified with oxygen vacancies are prepared. The oxygen vacancies in the material system can capture the photogenerated electrons activated in the SrTiO3 nanotubes and transfer them to the Ag nanoparticles anchored near them for photocatalytic reduction reaction, effectively realizing the spatial separation of photogenerated charges. At the same time, the presence of Schottky barriers at the heterojunction interface also inhibits the photogenerated electrons from flowing back to the SrTiO3 nanotubes, thereby preventing the recombination of photogenerated electrons and holes. The surface of the unmodified SrTiO3 sample is relatively smooth, and the diameter size is between 200 nm and 300 nm. The SrTiO3@OV@Ag sample synthesized after high-temperature hydrogenation and photoreduction treatment still maintains a one-dimensional nanotube structure with hollow characteristics, with a diameter of about 282 nm and a tube wall thickness of about 41 nm, and its surface shows the presence of many small Ag single-substance nanoparticles.
[0018] The oxygen vacancy modified SrTiO3@Ag nanotube disclosed in the present invention is applied in high-efficiency photocatalysts, and the improvement of the performance of semiconductor photocatalysts by multiple modifications is verified. The steps are as follows: (1) Preparation of SrTiO3 nanotubes: prepared by electrospinning. Strontium acetate was dissolved in a mixed solution of deionized water, anhydrous ethanol, dimethylformamide (DMF) and glacial acetic acid, and polyvinyl pyrrolidone (PVP) was slowly added. After stirring, butyl titanate (TBOT) was added and continued to stir until a uniform light yellow translucent solution was formed. A suitable needle model was selected, and the appropriate environmental factors such as temperature and humidity were adjusted through the temperature and humidity control system. The appropriate rotation speed, injection speed, step rate and other parameter values were set. The spinning solution was injected into the syringe, and a pure white polymer film was formed by electrospinning using an electrospinning machine, which was then dried and calcined. SrTiO3 nanotubes of white substance were prepared; (2) Synthesis of oxygen vacancy modified SrTiO3 nanotubes: Using the synthesized SrTiO3 sample as raw material, oxygen vacancy modified SrTiO3 nanotubes were synthesized by high temperature H2 reduction method; (3) Synthesis of oxygen vacancy modified SrTiO3@Ag nanotubes: The samples were prepared by photoreduction method based on oxygen vacancy modified SrTiO3 nanotubes. Specifically, the samples were dispersed in AgNO3 solution and stirred continuously to fully adsorb Ag. + , then irradiate the suspension with 365 nm ultraviolet light, and continue magnetic stirring during the irradiation process. Finally, the sample is separated from the liquid and washed several times with deionized water and then dried; (4) Study on the mechanism of oxygen vacancy modification of SrTiO3@Ag nanotubes: The photogenerated electron transfer behavior was studied using in situ irradiation XPS technology.
[0019] In step (2), the concentration of introduced oxygen vacancies is regulated according to the heating temperature (400 °C, 600 °C, 800 °C). The samples treated at different heating temperatures are named SrTiO3@OV-400, SrTiO3@OV-600, SrTiO3@OV-800, respectively. In particular, SrTiO3@OV-600 is represented as SrTiO3@OV.
[0020] In step (1), the stirring time is 8 to 12 h, the drying temperature is 60°C, the drying time is 10 to 15 h, the calcination time is 2 to 5 h, and the calcination temperature is 500 to 700°C. In step (3), the stirring time is 9 to 12 h, the illumination time is 30 to 90 min, the drying temperature is 60°C, and the drying time is 10 to 15 h.
[0021] In step (1), strontium acetate is dissolved in 5-6 mL of deionized water per gram, and then anhydrous ethanol, dimethylformamide (DMF) and glacial acetic acid are added in sequence and stirred to mix. Polyvinyl pyrrolidone (PVP) is slowly added to the mixed solution, and then magnetic stirring is performed for a long time, and the stirring time is 8-12 hours. Finally, butyl titanate (TBOT) is added and stirring is continued until a uniform light yellow translucent solution is formed.
[0022] In the step (1), the ratio of deionized water, anhydrous ethanol, dimethylformamide (DMF) and glacial acetic acid solution is 2:3:3:2. After the above solutions are mixed evenly, PVP is added and stirring is continued.
[0023] In step (2), the SrTiO3 nanotubes are evenly spread in a porcelain boat and placed in a tube furnace. The air in the tube furnace is evacuated using a vacuum pump, and then an argon-hydrogen mixed gas (H25%, Ar 95%) is continuously supplied at a certain rate. The temperature is raised to 400-800°C at a rate of 5-10°C / min and kept at this temperature for 1-3 hours.
[0024] In step (4), the prepared oxygen vacancy modified SrTiO3@Ag nanotubes were pasted on the surface of the conductive adhesive and sent to the XPS instrument for in-situ irradiation test. The irradiation light source was selected as ultraviolet light with a wavelength of 300nm. By observing the changes in the binding energy of the components before and after irradiation, the electron gain and loss situation was judged, and the photogenerated electron transfer behavior after the introduction of oxygen vacancies and Ag nanoparticles was studied.
[0025] The technical solution of the present invention is further described below in conjunction with specific embodiments: Example 1 The preparation of oxygen vacancy modified SrTiO3@Ag nanotubes with low oxygen vacancy is as follows: (1) Preparation of SrTiO3 nanotubes: prepared by electrospinning. 0.361 g of strontium acetate was dissolved in a mixed solution of 2 mL of deionized water, 3 mL of anhydrous ethanol, 3 mL of dimethylformamide (DMF) and 2 mL of glacial acetic acid, and 1.1 g of polyvinyl pyrrolidone (PVP) was slowly added, followed by magnetic stirring for 10 h. Finally, 0.6 mL of butyl titanate (TBOT) was added and stirring continued until a uniform light yellow translucent solution was formed. It was poured into a syringe equipped with a 22G metal needle for electrospinning. The jet pump propulsion speed was set to 0.08 mm / min, and the positive and negative voltages were 15 kV and -5 kV, respectively. The roller receiver was about 20 cm away from the needle and set to 30 revolutions per minute. After spinning, a pure white polymer film will be formed on the collector, which will then be placed in a 60 °C oven for drying, then collected in a crucible and placed in a muffle furnace for calcination at 600 °C in air for 3 h, with a heating rate of 2 °C / min. The white substance prepared by the above process is SrTiO3 nanotubes; (2) Synthesis of oxygen vacancy modified SrTiO3 nanotubes: The synthesized SrTiO3 sample was used as the raw material, and the oxygen vacancy modified SrTiO3 nanotubes were synthesized by high temperature H2 reduction method. During the synthesis process, 300 mg of SrTiO3 nanotubes were evenly spread in a porcelain boat and placed in a tube furnace. The air in the tube furnace was evacuated using a vacuum pump, and then an argon-hydrogen mixture (H25%, Ar 95%) was continuously supplied at a certain rate. The temperature was raised to 400°C at a rate of 5°C / min and kept at this temperature for 2h. (3) Synthesis of oxygen vacancy modified SrTiO3@Ag nanotubes: They were prepared by photoreduction method based on SrTiO3@OV nanotubes. Specifically, 300 mg of SrTiO3@OV sample was dispersed in 10 mL of AgNO3 solution and stirred for 10 h to fully adsorb Ag. + The suspension was then irradiated with 365 nm UV light for 1 h, with continuous magnetic stirring during the irradiation process. Photocatalytic reduction of Ag around the oxygen vacancies at the active sites of SrTiO3@OV nanotubes + Ag nanoparticles were formed, and finally the sample was separated from the liquid and washed with deionized water for several times and then dried; (4) Mechanism study of oxygen vacancy modified SrTiO3@Ag nanotubes: The oxygen vacancy modified SrTiO3@Ag nanotubes prepared in step (3) above were pasted on the surface of the conductive adhesive and then sent to the XPS instrument for in-situ irradiation test. The X-ray source target of the test instrument is an aluminum target with a power of 150 W and a ray energy of 1486 eV. The irradiation light source is a wavelength continuously adjustable strong light source, model PLS EM-150. The irradiation device installed on the side of the equipment is introduced into the cabin to irradiate the sample. The irradiation light source selects ultraviolet light with a wavelength of 300 nm.
[0026] Figure 1 (a) is the XRD spectrum of the prepared SrTiO3@Ag nanotubes modified with oxygen vacancies and different samples; (b) shows that the interplanar spacing of the hydrogenated samples is reduced and contains abundant oxygen vacancies. It can be seen from the figure that the diffraction peak intensity of SrTiO3@OV is significantly higher than that of SrTiO3, which is due to the increase in the crystallinity of the material after annealing. The diffraction peak intensity of the SrTiO3 cubic phase in SrTiO3@Ag and SrTiO3@OV@Ag is significantly lower than that of SrTiO3 and SrTiO3@OV, respectively, due to the influence of the loading of Ag nanoparticles. However, no characteristic peak belonging to Ag is observed, which is due to the low loading amount of Ag nanoparticles. This shows that the introduction of oxygen vacancies and Ag nanoparticles does not destroy the cubic phase structure of SrTiO3. It is worth mentioning that compared with the samples that have not been hydrogenated, the diffraction peak of the (110) crystal plane of the hydrogenated sample is slightly shifted toward a higher diffraction angle. Figure (c) shows the PL spectra of different photocatalysts at an excitation wavelength of 300 nm. The emission peaks of all samples are around 390 nm. The unmodified SrTiO3 nanotubes have the strongest emission peak, indicating that the photogenerated electrons and holes in the body recombine seriously. The introduction of oxygen vacancies or the loading of Ag nanoparticles on the surface of SrTiO3 nanotubes respectively reduced the PL emission peak intensity. SrTiO3@OV@Ag showed the strongest PL signal quenching, indicating that the recombination of photogenerated carriers was effectively suppressed, which is conducive to the enhancement of photocatalytic activity. In Figure (d), the larger the photocurrent, the higher the separation efficiency of photogenerated electron-hole pairs. It can be observed that SrTiO3@OV@Ag shows the largest photocurrent density under simulated solar radiation, which is much higher than other photocatalysts. Moreover, during several irradiation or light-shielding cycles, its photocurrent is reproducible and still maintains the strongest photoelectric conversion efficiency. This shows that the photogenerated electron-hole pair separation ability and light utilization ability of SrTiO3@OV@Ag are better than other samples. In addition, after shading treatment, the residual photocurrent of SrTiO3@OV@Ag is still higher than that of SrTiO3, indicating that the presence of oxygen vacancies and Ag nanoparticles inhibits the recombination of photogenerated carriers and thus prolongs the lifetime of photogenerated carriers.
[0027] Figure 2The (a, b) TEM images of the oxygen vacancy modified SrTiO3@Ag nanotubes prepared in Example 2 show that the SrTiO3@OV@Ag sample synthesized after high-temperature hydrogenation and photoreduction treatment still maintains a one-dimensional nanotube structure with hollow characteristics, with a diameter of about 282 nm and a tube wall thickness of about 41 nm.
[0028] Figure 3 In order to directly study the effects of oxygen vacancies and metal Ag on the photocatalytic performance of SrTiO3 nanotubes, the photocatalytic hydrogen evolution performance of different samples was tested under simulated solar irradiation, as shown in Figures a and b. SrTiO3 exhibits the lowest photocatalytic hydrogen evolution efficiency of only 8.91 µmol / g / h due to severe photogenerated carrier recombination. The introduction of oxygen vacancies (SrTiO3@OV) or the loading of Ag nanoparticles (SrTiO3@Ag) significantly improved the photocatalytic hydrogen evolution activity of the original SrTiO3 nanotubes, with average rates reaching 37.59 µmol / g / h and 48.25 µmol / g / h, respectively. The average photocatalytic hydrogen evolution rate of SrTiO3@OV@Ag reached 55.92 µmol / g / h, which is 6.28 times that of the unmodified SrTiO3 sample, indicating that the modification strategy of introducing oxygen vacancies and loading metal Ag can greatly improve the photocatalytic activity of SrTiO3.
[0029] Figure 4 Schematic diagram of the in-situ irradiation XPS device. The oxygen vacancy modified SrTiO3@Ag nanotubes are fixed on the surface of the sample stage by conductive glue. X-rays irradiate the sample to excite photoelectrons to escape from the material surface. After passing through the upper lens group and entering the hemispherical analyzer, the corresponding image is automatically drawn on the software according to the size of its kinetic energy. 300 nm ultraviolet light is introduced through the irradiation light source.
[0030] Figure 5 The photogenerated electron transfer behavior in the SrTiO3@OV@Ag photocatalytic system was studied by XPS testing. Ultraviolet light irradiation was introduced during the test, and the electron gain and loss were determined by observing the changes in the binding energy of the components before and after irradiation. 5 / 2 and Sr 3d 3 / 2 The two characteristic signal peaks of spin orbit changed from 133.03 eV and 134.82 eV before irradiation to 133.06 eV and 134.83 eV during irradiation. Moreover, the Ti 2p spectrum (Fig. b) is attributed to Ti 2p 3 / 2 and Ti 2p 1 / 2The positions of the two spin-orbit peaks were 458.36 eV and 464.09 eV before irradiation, and moved positively to 458.39 eV and 464.14 eV during irradiation. Furthermore, in the O 1s spectrum (Figure c), the two characteristic signal peaks assigned to lattice oxygen (Ti-O) and surface adsorbed oxygen (-OH) remained fixed at 529.60 eV and 533.51 eV, respectively, indicating that there was no electron flow or the electron flow was balanced in these two components. Interestingly, the characteristic signal peak of oxygen vacancies shifted positively with the largest offset, from 531.50 eV to 531.59 eV, indicating that electrons escaped from oxygen vacancies that were originally electron capture centers. Considering the relationship between electron cloud density and binding energy, and combining the binding energy changes of Sr 3d, Ti2p, and O 1s, it can be deduced that photogenerated electrons are transferred from SrTiO3 nanotubes to Ag nanoparticles loaded on the surface.
[0031] Example 2 The preparation steps of oxygen vacancy modified SrTiO3@Ag nanotubes are as follows: (1) Preparation of SrTiO3 nanotubes: prepared by electrospinning. 0.361 g of strontium acetate was dissolved in a mixed solution of 2 mL of deionized water, 3 mL of anhydrous ethanol, 3 mL of dimethylformamide (DMF) and 2 mL of glacial acetic acid, and 1.1 g of polyvinyl pyrrolidone (PVP) was slowly added, followed by magnetic stirring for 10 h. Finally, 0.6 mL of butyl titanate (TBOT) was added and stirring continued until a uniform light yellow translucent solution was formed. It was poured into a syringe equipped with a 22G metal needle for electrospinning. The jet pump propulsion speed was set to 0.08 mm / min, and the positive and negative voltages were 15 kV and -5 kV, respectively. The roller receiver was about 20 cm away from the needle and set to 30 revolutions per minute. After spinning, a pure white polymer film will be formed on the collector, which will then be placed in a 60 °C oven for drying, collected in a crucible and placed in a muffle furnace for calcination at 600 °C in air for 3 h, with a heating rate of 2 °C / min. The white substance prepared by the above process is SrTiO3 nanotubes; (2) Synthesis of oxygen vacancy modified SrTiO3 nanotubes: The synthesized SrTiO3 sample was used as the raw material, and the oxygen vacancy modified SrTiO3 nanotubes were synthesized by high temperature H2 reduction method. During the synthesis process, 300 mg of SrTiO3 nanotubes were evenly spread in a porcelain boat and placed in a tube furnace. The air in the tube furnace was evacuated using a vacuum pump, and then an argon-hydrogen mixture (H25%, Ar 95%) was continuously supplied at a certain rate. The temperature was raised to 600 °C at a rate of 5 °C / min and kept at this temperature for 2 h. (3) Synthesis of oxygen vacancy modified SrTiO3@Ag nanotubes: They were prepared by photoreduction method based on SrTiO3@OV nanotubes. Specifically, 300 mg of SrTiO3@OV sample was dispersed in 10 mL of AgNO3 solution and stirred for 10 h to fully adsorb Ag. + The suspension was then irradiated with 365 nm UV light for 1 h, with continuous magnetic stirring during the irradiation process. Photocatalytic reduction of Ag around oxygen vacancies at the active sites of SrTiO3@OV nanotubes + Ag nanoparticles were formed, and finally the sample was separated from the liquid and washed with deionized water for several times and then dried.
[0032] Example 3 The steps for preparing oxygen vacancy modified SrTiO3@Ag nanotubes with high oxygen vacancy are as follows: (1) Preparation of SrTiO3 nanotubes: prepared by electrospinning. 0.361 g of strontium acetate was dissolved in a mixed solution of 2 mL of deionized water, 3 mL of anhydrous ethanol, 3 mL of dimethylformamide (DMF) and 2 mL of glacial acetic acid, and 1.1 g of polyvinyl pyrrolidone (PVP) was slowly added, followed by magnetic stirring for 10 h. Finally, 0.6 mL of butyl titanate (TBOT) was added and stirring continued until a uniform light yellow translucent solution was formed. It was poured into a syringe equipped with a 22G metal needle for electrospinning. The jet pump propulsion speed was set to 0.08 mm / min, and the positive and negative voltages were 15 kV and -5 kV, respectively. The roller receiver was about 20 cm away from the needle and set to 30 revolutions per minute. After spinning, a pure white polymer film will be formed on the collector, which will then be placed in a 60 °C oven for drying, collected in a crucible and placed in a muffle furnace for calcination at 600 °C in air for 3 h, with a heating rate of 2 °C / min. The white substance prepared by the above process is SrTiO 3 Nanotubes; (2) Synthesis of oxygen vacancy modified SrTiO3 nanotubes: The synthesized SrTiO3 sample was used as the raw material, and the oxygen vacancy modified SrTiO3 nanotubes were synthesized by high temperature H2 reduction method. During the synthesis process, 300 mg of SrTiO3 nanotubes were evenly spread in a porcelain boat and placed in a tube furnace. The air in the tube furnace was evacuated using a vacuum pump, and then an argon-hydrogen mixture (H25%, Ar 95%) was continuously supplied at a certain rate. The temperature was raised to 800 °C at a rate of 5 °C / min and kept at this temperature for 2 h. (3) Synthesis of oxygen vacancy modified SrTiO3@Ag nanotubes: They were prepared by photoreduction method based on SrTiO3@OV nanotubes. Specifically, 300 mg of SrTiO3@OV sample was dispersed in 10 mL of AgNO3 solution and stirred for 10 h to fully adsorb Ag. + The suspension was then irradiated with 365 nm UV light for 1 h, with continuous magnetic stirring during the irradiation process. Photocatalytic reduction of Ag around oxygen vacancies at the active sites of SrTiO3@OV nanotubes + Ag nanoparticles were formed, and finally the sample was separated from the liquid and washed with deionized water for several times and then dried.
[0033] The above is a detailed introduction to the in-situ test method for studying the electron transport mechanism of SrTiO3@Ag nanotube photocatalysts modified with oxygen vacancies provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. An in-situ testing method for studying the electron transport mechanism of SrTiO3@Ag nanotube photocatalysts modified with oxygen vacancies, characterized in that: Here are the steps: (1) Synthesis of oxygen vacancy modified SrTiO3@Ag nanotubes: SrTiO3 nanotubes were obtained by electrospinning, and then reduced with high temperature H2 and dispersed in AgNO3 solution with continuous stirring. The suspension was then irradiated with ultraviolet light and continuously stirred magnetically. Finally, the product was separated from the liquid and washed with water for multiple times before drying to obtain oxygen vacancy modified SrTiO3@Ag nanotubes. (2) In-situ test method: SrTiO3@Ag nanotubes are pasted on the surface of the conductive adhesive and sent to the XPS instrument for in-situ irradiation test. During the pre-vacuuming process, all light sources in the transition chamber and the test chamber are turned off to place the sample in a completely dark environment. After the pre-vacuuming is completed, the test process is also kept in complete darkness. At this time, the test results are the data under dark conditions; 350 nm ultraviolet light is added, and the test results are the data under light conditions.
2. The in-situ testing method for studying the electron transport mechanism of SrTiO3@Ag nanotube photocatalysts modified with oxygen vacancies according to claim 1, characterized in that: In step (1), the stirring time is 8 to 12 h, the drying temperature is 50 to 60 ° C, the drying time is 10 to 15 h, the calcination time is 2 to 5 h, and the calcination temperature is 500 to 700 ° C.
3. The in-situ testing method for studying the electron transport mechanism of SrTiO3@Ag nanotube photocatalysts modified with oxygen vacancies according to claim 1, characterized in that: In step (1), electrospinning is used to prepare nanofibers, a suitable needle model is selected, and suitable environmental factors such as temperature and humidity are adjusted through a temperature and humidity control system, and suitable electrospinning parameters are set: the polymer solution flow rate is 0.5~2.0 mL / h, the roller speed is 80~200 rpm, the voltage is 12~25 kV, and the receiving distance between the syringe and the electrospinning receiving roller is 8~20 cm; the environmental parameters are adjusted: the ambient temperature is 20~28 °C, the ambient humidity is 40%~60%, the precursor solution is injected into a syringe with a needle, a high voltage static of 20 kV is applied to the needle, and a grounded rotating roller is used to receive the fiber.
4. The in-situ testing method for studying the electron transport mechanism of SrTiO3@Ag nanotube photocatalysts modified with oxygen vacancies according to claim 1, characterized in that: In the step (1), the calcination process is to heat the temperature in a muffle furnace at a rate of 1-3 °C / min to 500-700 °C, keep the temperature for 2-5 h, dissolve strontium acetate in 5-6 mL of deionized water per gram, then add anhydrous ethanol, dimethylformamide and glacial acetic acid in sequence and stir to mix, slowly add polyvinyl pyrrolidone to the mixed solution, and then perform long-term magnetic stirring for 8-12 h, finally add butyl titanate and continue stirring until a uniform light yellow translucent solution is formed.
5. The in-situ testing method for studying the electron transport mechanism of SrTiO3@Ag nanotube photocatalysts modified with oxygen vacancies according to claim 1, characterized in that: In the step (1), the SrTiO3 nanotubes are evenly spread in a porcelain boat and placed in a tube furnace. The air in the tube furnace is evacuated using a vacuum pump, and then an argon-hydrogen mixed gas is continuously supplied at a certain rate, and the temperature is increased to 400-800°C at a rate of 5-10°C / min, and kept at this temperature for 1-3 hours.
6. The in-situ testing method for studying the electron transport mechanism of SrTiO3@Ag nanotube photocatalysts modified with oxygen vacancies according to claim 1, characterized in that: In the argon-hydrogen mixed gas in step (1), the volume fraction of H2 is 5%, and the volume fraction of Ar is 95%.
Citation Information
Patent Citations
Preparation method of strontium titanate nanotube material
CN105401260A
Multilayer TiO2 nanotube-based photocatalyst and preparation method and application thereof
CN107376912A
Method for preparing oxygen-vacancy-containing strontium titanate photocatalyst
CN107552033A
Silver-loaded modified strontium titanate catalyst as well as preparation method and application thereof
CN110639520A
Preparation method of black TiO2 nanosheet photocatalyst
CN111821966A